Qualitative Study of the Wishes of the Elderly in Tehran - Yousefi, Zahra; Mahmoudi , Zahra (KMAN Counseling & Psychology Nexus, 2023)
This study aimed to qualitatively explore the range and nature of wishes among the elderly, considering demographic variables, to better understand their needs and aspirations during old age. Employing a phenomenological approach, the research analyzed data from in-depth interviews with 100 seniors, focusing on their expressed wishes and desires. Purposeful sampling was utilized to ensure a diverse representation of demographic backgrounds. Analysis revealed seven categories of elderly wishes: health and happiness, family desires, desire for death, seeking meaning, worldly desires, homeland desires, and personal security, with health and family being predominant. The findings underscore the significance of health maintenance and family support in the well-being of the elderly, suggesting that these areas should be prioritized in care strategies and policy planning. The study contributes to a deeper understanding of elderly needs, facilitating more targeted and effective support mechanisms.